Learning strategies with television series: simple attitudes to improve oral skills (Research, Society and Development, 2021)
The exposure to authentic materials as TV series provides students with motivating, useful, and contextualized vocabulary, as well as the opportunity to observe language being spoken by natives during real-life circumstances. Though, solely exposure to the language may not be sufficient to improve students’ language abilities. Thereat, this research aimed at investigating how television series can assist students’ oral abilities; by examining what mechanisms (learning strategies) students most use to properly comprehend the dialogues presented in such programs, as well as to observe students' perception of their listening and speaking abilities. The methodology adopted in this study was exploratory, with the approach to the research occurring quantitatively and qualitatively, by field research, through a questionnaire administration, and a literature review examination. This study demonstrated that the importance of exposure to the target language resides thoroughly on students' attitudes towards the material, rather than to the pure amount of exposure on itself, the strategies learners employ to manipulate the information, and to monitor their understanding are primary determinants for language acquisition. In conclusion, the study demonstrated to teachers the necessity of practicing such strategies and to students the relevance of developing control of their language learning process, therefore becoming autonomous learners.